Ties That Bond: Youth Sport as a Vehicle for Social Identity and Positive Youth Development. Issue 2 (3rd April 2017) - Bruner, Mark W.; Balish, Shea M.; Forrest, Christopher; Brown, Sarah; Webber, Kristine; Gray, Emily; McGuckin, Matthew; Keats, Melanie R.; Rehman, Laurene; Shields, Christopher A.
ABSTRACT: An emerging area of research has focused on understanding how the group dynamics of a sport team influence positive youth development (PYD). The identities that youth form through their membership in sport teams (i.e., social identities) have been found to influence teammate behavior and team performance. Yet, minimal work exists on social identity and PYD in youth sport.Purpose : The purpose of this study was to investigate the relationship between social identity and PYD in sport.Method : Youth engaged in recreational sport ( N  = 219; M age  = 11.61 years, SD  = 1.39 years) completed measures of social identity and PYD in sport. The social identity measure assessed 3 dimensions including ingroup ties (IGT; perceptions of similarity, bonding, belongingness), cognitive centrality (importance of being a team member), and ingroup affect (IGA; feelings associated with group membership). A regression analysis was performed separately for 4 PYD outcomes (personal and social skills, goal setting, initiative, negative experiences) with the 3 dimensions of social identity entered as predictors.Results : Regression analyses revealed that IGT and IGA were positively associated with personal and social skills ( R 2 Adj. = .29). Further, IGT predicted initiative ( R 2 Adj. = .16), whereas IGA was positively associated with goal setting ( R 2 Adj. = .17) and negatively associated with negative experiences ( R 2 Adj. = .08).Conclusion : The findings extend previous research highlighting the benefits of social identity on teammate behavior and team performance and demonstrate how social identity may contribute to PYD through sport.